Community of Practice, Andragogical Learning, and Spiritual Resilience among Ojol Drivers: The Ojol Mengaji Case in Yogyakarta - Rakan, Muhammad Aushaf; Makrufi, Anisa Dwi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Platform-based motorcycle-taxi drivers in Indonesia work under conditions marked by income uncertainty, irregular demand, and limited employment protection. Although religious communities may provide social and spiritual resources, little is known about how profession-based religious learning is organized in response to the occupational circumstances of gig workers. This study examines how Community of Practice (CoP) arrangements and andragogical learning practices are experienced in relation to participants’ accounts of spiritual resilience in the Ojol Mengaji community in Yogyakarta. Using a qualitative single-case design, the study involved four purposively selected participants: an executive committee member, a religious instructor, a member with a convert background, and a member without a convert background. Data were collected through semi-structured interviews, direct observation of one community session, and a review of attendance records and learning-module frameworks. The data were analyzed through condensation, display, and conclusion drawing and verification. The findings indicate that Quranic learning provided a shared domain, while a common occupational identity facilitated peer interaction and mutual assistance. Off-peak scheduling, flexible attendance, gradual correction, and attention to participants’ prior experiences made religious learning more compatible with adult platform workers’ circumstances. Participants associated these arrangements with greater comfort in Quranic learning, social connection, and continued religious engagement alongside work. The findings suggest that individual spiritual meaning-making may be supported through community relationships and context-responsive learning. This study contributes a context-specific account of how profession-based nonformal religious education can connect occupational solidarity, adult learning, and spiritual meaning-making under precarious working conditions.